2012
DOI: 10.1007/s10964-012-9832-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Neighborhood and Family Factors with Trajectories of Physical and Social Aggression During Adolescence

Abstract: Adolescents develop within multiple contexts that synergistically influence their behavior and health. To understand the simultaneous influence of neighborhood and family contexts on adolescents, this study examined relationships of neighborhood socioeconomic disadvantage, neighborhood social disorganization, family conflict, parent-child bonding and parental control with trajectories of physical and social aggression. The sample included 5,118 adolescents between ages 11 and 18 (50% female, 52% Caucasian) liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 84 publications
1
19
0
1
Order By: Relevance
“…Although parental hostility is only one of several factors that render risk for increased aggressive behavior among adolescents, parental hostility is linked with a number of other factors also associated with risk (Farrington 2005). Thus, our findings likely extend to other domains of risk for aggressive behavior problems during adolescence such as low parental monitoring (Low et al 2012), psychological control (Murray et al 2014), and neighborhood and socioeconomic disadvantage (Karriker-Jaffe et al 2013). …”
Section: Discussionmentioning
confidence: 64%
“…Although parental hostility is only one of several factors that render risk for increased aggressive behavior among adolescents, parental hostility is linked with a number of other factors also associated with risk (Farrington 2005). Thus, our findings likely extend to other domains of risk for aggressive behavior problems during adolescence such as low parental monitoring (Low et al 2012), psychological control (Murray et al 2014), and neighborhood and socioeconomic disadvantage (Karriker-Jaffe et al 2013). …”
Section: Discussionmentioning
confidence: 64%
“…Accordingly, the results of the current study revealed that other critical predictors of physical aggressive behavior, such as peer delinquency (Zimmerman & Messner, 2011) and parenting styles (Brody et al, 2001), may exert a greater influence on the outcome than neighborhood disadvantage among boys. Numerous studies have also found that neighborhood structural factors have indirect effects on aggression (Bernburg & Thorlindsson, 2007;Maimon & Browning, 2010;Obeidallah et al, 2004), acting synergistically with other factors in shaping the behavior of children and adolescents (Hart & Marmorstein, 2009;Karriker-Jaffe, Foshee, Ennett & Suchindran, 2013;Oberwittler, 2007). The imbalance between these factors or the differential vulnerability to risk environments between boys and girls may lead to varying effects of neighborhood disadvantage on the outcome (Kroneman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Social ecological theories (e.g., Bronfenbrenner, 1979) also emphasize the role of the neighborhood context in shaping development and also recognize the importance of other social influences, such as peer interactions and family processes. Guided by these theories, studies have increasingly examined the impact of neighborhood context on adolescent development (e.g., Ennett et al, 2008; Karriker-Jaffe et al, 2013; Lambert et al, 2004; Sampson, 2012; Tobler et al, 2009; Zimmerman and Messner, 2011). …”
Section: Introductionmentioning
confidence: 99%